Kemampuan Menulis Surat Resmi Siswa Kelas VII MTSN 1 Padang Menggunakan Teknik Pemodelan - Dwi Muthia Chan; Susanti Marisya; Selvia Anggria Nengsih (Kilau Publishing, 2025)
This research is based on the fact that many students have difficulty in writing exposition texts, especially in determining the main idea, formulating problems, and choosing appropriate words and language to compose the thesis, arguments, and reaffirmation sections. The purpose of this study is to describe and explain the ability to write exposition texts based on the discovery learning model in phase X students at SMA Negeri 8 Padang. This study uses a quantitative descriptive approach. Data were obtained through performance tests and documentation, then analyzed by assessing students' writing results, giving scores, converting scores into grades, calculating averages, discussing, and drawing conclusions. The results showed that the ability to write exposition texts with the discovery learning model was in the very good category, with an average value of 86.72, which was in the range of 86-95 on a scale of 10. This proves that the discovery learning model is effective in improving students' text writing, especially in the aspects of developing theses, arguments, and reaffirmation.